An IMiD-inducible degron provides reversible regulation for chimeric antigen receptor expression and activity. Issue 6 (17th June 2021) - Carbonneau, Seth; Sharma, Sujata; Peng, Liaomin; Rajan, Vaisakh; Hainzl, Dominik; Henault, Martin; Yang, Chian; Hale, Jacob; Shulok, Janine; Tallarico, John; Porter, Jeff; Brogdon, Jennifer L.; et al.
Summary: The recent development of successful CAR (chimeric antigen receptor) T cell therapies has been accompanied by a need to better control potentially fatal toxicities that can arise from adverse immune reactions. Here we present a ligand-controlled CAR system, based on the IKZF3 ZF2 β-hairpin IMiD-inducible degron, which allows for the reversible control of expression levels of type I membrane proteins, including CARs. Testing this system in an established mouse xenotransplantation model for acute lymphoblastic leukemia, we validate the ability of the CAR19-degron to target and kill CD19-positive cells displaying complete control/clearance of the tumor. We also demonstrate that the activity of CAR19-degron can be regulated in vivo when dosing a US Food and Drug Administration-approved drug, lenalidomide. Graphical abstract: Highlights: CAR-IKZF3 degron expression and CART activity can be regulated in vitro IMiD treatment controls CART-IKZF3 anti-tumor efficacy in vivo Such strategy aims to mitigate potential toxicities associated with CART therapy The IKZF3/lenalidomide pair is portable to other membrane proteins Abstract : Carbonneau et al. describe a strategy to control the expression levels of membrane proteins of interest, including chimeric antigen receptors displayed in T cells (CARTs). The authors demonstrate that this strategy allows controlling CART anti-tumor activity, in vivo, and discuss the unique features enabling a fast path into clinical development.